Synergy between chloride salts (Na+, K+, Ca2+) and ozonation in the simultaneous modification of pigmented rice starch - Raphael Lucas Jacinto Almeida; Newton Carlos Santos; Iêda Letícia de Souza Ferreira; Raphael da Silva Eduardo; Vitoria de Andrade Freire; Maely Jezzer Cândido Venâncio; Lucas Wallyson Pereira de Queiroz; Osmar Batista de Souza Neto; Alison Bruno Borges de Sousa; Ellen Cristina Nabiça Rodrigues; Elizabete de Oliveira Araújo; Mateus Sabino de Souza Ferreira; et al. (Food Chemistry, 2026)

Antimicrobial activity and insecticidal evaluation of Passiflora edulis Sims. (Passifloraceae) - Adrielle Rodrigues Costa; Saulo Almeida Menezes; José Weverton Almeida-Bezerra; Severino Denicio Gonçalves de Sousa; Dhenes Ferreira Antunes; Elaine Cristina Conceição de Oliveira; Janaína de Souza Bezerra; Dieferson Leandro de Souza; Eveline Naiara Nuvens Oliveira; Francisca de Fátima Silva de Sousa; Maria Aparecida Barbosa Ferreira Gonçalo; Germana de Alencar Maia Luz; et al. (Vegetos, 2025)

A GPS signal-in-space simulation model for equatorial and low latitudes in the Brazilian longitude sector - Teddy Modesto Surco Espejo; Emanoel Costa; Alison O. Moraes; André Ricardo Fazanaro Martinon; Eurico Rodrigues de Paula; João Francisco Galera Monico (GPS Solutions, 2022)

Mismatch between bird species sensitivity and the protection of intact habitats across the Americas - Victor Cazalis; Megan D. Barnes; Alison Johnston; James E. M. Watson; Cagan H. Şekercioğlu; Ana S. L. Rodrigues (Ecology Letters, 2021)
Protected areas are highly heterogeneous in their effectiveness at buffering human pressure, which may hamper their ability to conserve species highly sensitive to human activities. Here, we use 60 million bird observations from eBird to estimate the sensitivity to human pressure of each bird species breeding in the Americas. Concerningly, we find that ecoregions hosting large proportions of high‐sensitivity species, concentrated in tropical biomes, do not have more intact protected habitat. Moreover, 266 high‐sensitivity species have little or no intact protected habitat within their distributions. Finally, we show that protected area intactness is decreasing faster where high‐sensitivity species concentrate. Our results highlight a major mismatch between species conservation needs and the coverage of intact protected habitats, which likely hampers the long‐term effectiveness of protected areas at retaining species. We highlight ecoregions where protection and management of intact habitats, complemented by restoration, is urgently needed.

An update on potential links between type 2 diabetes mellitus and Alzheimer’s disease - Ricardo Augusto Leoni De Sousa; Alison R. Harmer; Daniel Almeida Freitas; Vanessa Amaral Mendonça; Ana Cristina Rodrigues Lacerda; Hércules Ribeiro Leite (Molecular Biology Reports, 2020)

Genetic and physiological analysis of early drought response in Manihot esculenta and its wild relative - Carolina Vianna Morgante; Sávio Luiz Pereira Nunes; Agnaldo Rodrigues de Melo Chaves; Cláudia Fortes Ferreira; Saulo de Tarso Aidar; Alison Borges Vitor; Eder Jorge de Oliveira (Acta Physiologiae Plantarum, 2020)

New GJA8 variants and phenotypes highlight its critical role in a broad spectrum of eye anomalies - Fabiola Ceroni; Domingo Aguilera-Garcia; Nicolas Chassaing; Dorine Arjanne Bax; Fiona Blanco-Kelly; Patricia Ramos; Maria Tarilonte; Cristina Villaverde; Luciana Rodrigues Jacy da Silva; Maria Juliana Ballesta-Martínez; Maria Jose Sanchez-Soler; Richard James Holt; et al. (Human Genetics, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Acute liver effects, disposition and metabolic fate of [14C]-fenclozic acid following oral administration to normal and bile-cannulated male C57BL/6J mice - Kathryn Pickup; Scott Martin; Elizabeth A. Partridge; Huw B. Jones; Jonathan Wills; Tim Schulz-Utermoehl; Alan McCarthy; Alison Rodrigues; Chris Page; Kerry Ratcliffe; Sunil Sarda; Ian D. Wilson (Archives of Toxicology, 2017)

On the distribution of GPS signal amplitudes during low-latitude ionospheric scintillation - Alison de Oliveira Moraes; Eurico Rodrigues de Paula; Waldecir João Perrella; Fabiano da Silveira Rodrigues (GPS Solutions, 2013)

In vitro exploration of potential mechanisms of toxicity of the human hepatotoxic drug fenclozic acid - Alison V. M. Rodrigues; Helen E. Rollison; Scott Martin; Sunil Sarda; Timothy Schulz-Utermoehl; Simone Stahl; Frida Gustafsson; Julie Eakins; J. Gerry Kenna; Ian D. Wilson (Archives of Toxicology, 2013)

Analysis of the Characteristics of Low-Latitude GPS Amplitude Scintillation Measured During Solar Maximum Conditions and Implications for Receiver Performance - Alison de Oliveira Moraes; Fabiano da Silveira Rodrigues; Waldecir João Perrella; Eurico Rodrigues de Paula (Surveys in Geophysics, 2012)